2017
DOI: 10.1093/jpepsy/jsx146
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Problem Areas in Diabetes: Teen and Parent of Teen Versions

Abstract: The PAID-T and P-PAID-T are valid, reliable, and useful measures of diabetes-specific distress for teenagers with type 1 diabetes and parents of teenagers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
84
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 40 publications
8
84
0
1
Order By: Relevance
“…Scores were calculated using the full 26‐item test and an abbreviated 14‐item version with a preliminary cutoff score of ≥44. This cutoff was associated with higher HbA1c, depressive symptoms, and anxiety 22 …”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Scores were calculated using the full 26‐item test and an abbreviated 14‐item version with a preliminary cutoff score of ≥44. This cutoff was associated with higher HbA1c, depressive symptoms, and anxiety 22 …”
Section: Methodsmentioning
confidence: 89%
“…This cutoff was associated with higher HbA1c, depressive symptoms, and anxiety. 22 The SCI-R is a 15-item self-report questionnaire assessing patients' perceptions of diabetes-related health behaviors and is described elsewhere. 23 The Pediatric Quality of Life Inventory and school functioning subscale and is described in greater detail elsewhere.…”
Section: Physiological Outcome Measuresmentioning
confidence: 99%
“…14,33,34 The resilience intervention tested in the STePS study contained components that have been shown to help address DRD, including cognitive-behavioral skills. 10,35 Targeted clinical screening of DRD with existing validated measures 36,37 can efficiently identify adolescents needing intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The study did not include measurement of many other psychological variables that could mediate or moderate DA use such as health locus of control, 38 diabetes-related self-efficacy, 39 diabetes-related distress, 40 or family conflict. 41 By including measurement of such mechanisms, future studies of DA utilization could illuminate the psychological processes that influence individuals’ benefit from SDM interventions.…”
Section: Discussionmentioning
confidence: 99%